Nutritional Value Composition Of Lamun Fruit Enhalus Acoroides From Samboang Beach, Bulukumba District, Sulawesi Selatan - Minsas, Sukal; Warsidah; Irwan (Jurnal Ilmiah Platax, 2024)
As the main producer, seagrass leaves are the main food for several marine animals such as turtles and dugongs, while seagrass fruit which contains soft seeds can be consumed as food for humans, but it is not very popular and there is not much information regarding the nutritional content of seagrass fruit. One species of seagrass that is often found in the waters of Samboang Beach, Bulukumba Regency is the Enhalus acoroides species. This research aims to determine the proximate and essential metal content of Enhalus acoroides seagrass fruit taken from Samboang coastal waters, Bulukumba Regency, South Sulawesi. Determination of proximates, namely proteins, was carried out using the Kjeldahl method, fats using the extraction method with n-hexane solvent and essential metals, and while determination of essential metal content using the atomic absorption spectrophotometry method. The results of this research show that the water content is 87%, the ash content is 0.76%, the protein content is 1.2%, the fat content is 0.66% and the carbohydrate content is 10.38%. The essential metal test results show zinc (Zn) levels of 5.32 ppm, iron (Fe) of 7.2 ppm, and cobalt (Co) of 0.11 ppm. Keywords: Enhalus acoroides, proximate, protein, Samboang beach, essential Abstrak Sebagai produsen utama, daun lamun merupakan makanan utama dari beberapa hewan laut seperti penyu dan dugong sedangkan buah lamun yang mengandung biji yang lunak dapat dikonsumsi sebagai pangan untuk manusia, tetapi belum begitu populer dan informasi terkait kandungan gizi dari buah lamun tersebut belum banyak ditemukan. Salah satu spesies lamun yang banyak ditemukan di perairan Pantai Samboang Kabupaten Bulukumba adalah dari jenis Enhalus acoroides. Penelitian ini bertujuan untuk menentukan kandungan proksimat dan logam esensial dari buah lamun Enhalus acoroides yang diambil dari perairan pantai Samboang Kabupaten Bulukumba Sulawesi Selatan. Penentuan proksimat yaitu protein dilakukan dengan metode kjeldahl, lemak menggunakan metode ekstraksi dengan pelarut n-heksan dan logam esensial, sedangkan penentuan kandungan logam esensial dengan menggunakan metode spektrofotometri serapan atom. Dari hasil penelitian ini menunjukkan kadar air sebesar 87%, kadar abu sebesar 0.76%, kadar  protein sebesar 1.2 %, kadar lemak sebesar 0.66% dan kadar karbohidrat sebesar  10.38 %. Pada hasil pengujian logam esensial menunjukkan kadar logam zink (Zn) sebesar 5.32 ppm, besi (Fe) sebesar 7.2 ppm dan kobalt (Co) sebesar 0.11 ppm Keywords: Enhalus acoroides, proksimat, protein, Samboang beach, essensial